Growth and Characterization of New Semi-Organic L-Asparagine Potassium Di-Hydrogen Phosphate Crystals - Neelakantaprasad, B.; Jegatheesan, A.; Murugan, J.; Aroulmoji, V.; Rajarajan, G. (Asian Journal of Chemistry, 2013)
The studies on the growth and characterization of a new semi-organic non-linear optical crystal, L-asparagine potassium dihydrogen phosphate have been successfully carried out by slow evaporation technique using deionized water as a solvent. The grown crystal is characterized by powder X-ray diffraction analysis and FT-IR analysis. The results of X-ray diffraction analysis showed that it possess orthogonal structure having lattice parameters a = 5.582 Å, b = 9.812 Å and c = 11.796 Å, a = b = g = 90° and V = 514 Å3. The fourier transform infrared spectroscopy of L-asparagine potassium dihydrogen phosphate crystal were recorded between wave-number 4000 to 400 cm–1 showed very weak bands appearing around 1232 and 1147 cm–1 are due to P–O–H stretching and bending. The observed broad intense band in 3385-3119 cm–1 region is assigned to NH stretch of NH2 vibration of L-asparagine potassium dihydrogen phosphate molecule. The CH2 vibration of the amino acid shows its peak at 2945 cm–1. The combination band observed at 2149 cm–1 is due to asymmetric NH3+ vibration at 1643 cm–1 and NH2+ tensional oscillation at 512 cm–1 and optical transmission spectral analysis. The lower cut off wavelength of L-asparagine potassium dihydrogen phosphate crystal occurs at 198 nm and it reveals that the material has good optical transparency in the entire visible region. The results of hardness test showed that the presence of dopant has enhanced the mechanical strength of the L-asparagine potassium dihydrogen phosphate crystals and the second harmonic generation of L-asparagine potassium dihydrogen phosphate crystals was tested using Kurtz and Perry method also showed good results.